Comparison of manikin carry performance by lifeguards and lifesavers when using barefoot, flexible and fiber fins - Abraldes, J. A.; Soares, S; Lima, A. B.; Fernandes, R. J.; Vilas-Boas, J. P. (Biomechanics and Medicine in Swimming XI, 2010)
The use of fins is fundamental in aquatic sport and saving rescue activities , large variety of models existing in the market. The main purpose of this study was to compare two groups (lifeguards and lifesavers) performing a manikin carry effort using barefoot, flexible and fibre fins. Ten licensed lifeguards and ten lifesavers performed 3 x 25 m with barefoot, flexible and fibre fins in manikin carry connected to a cable speedometer that measured instantaneous velocity (v). For lifesavers, fibre fins allowed higher v values compared with flexible fins. No differences between fins models were observed regarding v of lifeguards. Additionally, the use of flexible or fibre fins do not show differences in fatigue index for both groups.